KIF15 plays a role in promoting the tumorigenicity of melanoma. (August 2019) - Yu, Xiaoyu; He, Xiaoyu; Heindl, L.M.; song, Xin; Fan, Jiayan; Jia, Renbing
Abstract: Kinesins are a superfamily of motor proteins and are often dysregulated in many cancers. KIF15, which belongs to the kinesin-12 family, has been shown to function in many different cellular processes, including proliferation, apoptosis, differentiation and development. However, the role of KIF15 in melanoma, remains unknown. In this study, the expression levels of KIF15 in melanoma cells lines and tissues were determined via real-time PCR, immunohistochemical staining and western blot. The effect of KIF15 on tumorigenesis was evaluated by using MTT and colony information. The function of KIF15 on cell survival was detected through flow cytometry assay. Microarray assay and bioinformatics analysis were used to find the potential target of KIF15 . We show that KIF15 was significantly upregulated in melanoma cells and tissues. The suppression of KIF15 in tumors significantly reduced tumor growth and increased apoptosis in A375 and OCM1 cells. Findings based on the subcutaneous xenograft model were further consistent with the in vitro results that KIF15 knockdown inhibited melanoma tumor growth in vivo . Microarray assay and bioinformatics indicated that BIRC5, CDK4 and WNT5A were three potential targets of KIF15 . Taken together, our results suggest that KIF15 plays a positive role in the tumorigenicity of melanoma and it may serve as a novel diagnostic and therapeutic target for melanoma, especially uveal melanoma. Highlights: KIF15 was significantly upregulated in melanoma cells and tissues Demonstrated that KIF15 was an oncogene in melanoma KIF15 promotes tumorigenesis by upregulated its downstream targets, BIRC5, CDK4 and WNT5A